A comparative evaluation of dermatoglyphics in different classes of malocclusion - Garima Jindal; Ramesh Kumar Pandey; Sameer Gupta; Meera Sandhu (Elsevier, 2015)
Aim: To study associations of dermatoglyphic features with malocclusion in Indian children. Materials and methods: A total of 237 children aged 12-16 years, who attended our outpatient clinic in a government medical college, were selected. Finger and palm prints were collected, and fingertip pattern frequencies, total ridge counts (TRCs), and atd angles (formed by the triradii below the first and last digits and that in the hypothenar region of the palm) were calculated. These parameters were analyzed with their Angle's class of malocclusion using appropriate statistical tests. Dermatoglyphic parameters were examined and asymmetry analysis was conducted in subjects with different occlusion patterns. Results: Although no fingerprint pattern was found to be specific for a particular class of occlusion, increased tendencies toward high frequencies of whorls in subjects with class II malocclusion and plain arches in those with class III malocclusion were observed. Significant differences in atd angle and TRC were observed among malocclusion types (p = 0.0001). Asymmetry scores did not differ significantly. Conclusion: Dermatoglyphic analysis can be used as an indicator of malocclusion at an early age, thereby aiding the development of treatments aiming to establish favorable occlusion. Inheritance and twin studies, as well as those conducted in different ethnic groups, are required to examine these relationships further. Keywords: Dermatoglyphics, Malocclusion, Asymmetry